The Bright and Dark Side of Eudaimonic Emotions: A Conceptual Framework - Helen Landmann (Media and Communication, 2021)
Based on a review of eudaimonic emotion concepts, definitional and empirical overlaps between the concepts are identified and a framework of eudaimonic emotions is developed. The framework proposes that feelings of elevation, awe, tenderness, and being moved can be differentiated based on their feeling components, thus constituting the feeling-specific types of eudaimonic emotions. A variety of other emotion concepts rely on reference to their elicitors, such as moral elevation (i.e., being moved by moral virtue), aesthetic awe (i.e., being moved by beauty), kama muta (i.e., being moved by communal sharing) and admiration (i.e., being moved by achievements), thus constituting elicitor-specific types of eudaimonic emotions. Structuring eudaimonic emotions along these lines allows for integrating research on these emotions. This integration leads to the proposition of general eudaimonic effects and value-specific effects of positive eudaimonic emotions on behaviour. Considering these effects can enhance understanding of how positive eudaimonic emotions affect pro-social intentions—the bright side of being moved—as well as the manipulating effects of propaganda—the dark side of being moved.